A method for analyzing instructors' purposeful modifications to research-based instructional strategies - Erin Scanlon; Brian Zamarripa Roman; Elijah Ibadlit; Jacquelyn J. Chini (SpringerOpen, 2019)
Abstract Background Numerous studies in the literature describe the effectiveness of research-based instructional strategies (RBIS) in the postsecondary STEM (science, technology, engineering, and mathematics) context. Many of these studies are predicated on the assumption that instructors implement the RBIS exactly as is intended by the developers. However, by necessity, instructors modify the RBIS to suit their needs and to best support their students. The purpose of this commentary is to describe a framework (Modification Identification Framework) and method (Revealed Causal Mapping) for classifying modifications instructors make to an RBIS as they implement it in their course and identify the reasons why instructors make these modifications. As the MIF was developed in the healthcare field, we altered and extended it to be suitable for educational settings. We then demonstrate the usefulness of the framework and method through an extended sample study of instructors' modifications to the Student-Centered Active Learning Environment with Upside-Down Pedagogies (SCALE-UP) model in introductory physics. Conclusions In general, the findings from investigations with the Modification Identification Framework and Revealed Causal Mapping can be used to identify what experiences lead instructors to modify certain aspects of RBIS. These findings can aid curriculum developers in creating supports for instructors so they can make changes in line with the underlying structure and theory of the RBIS.